Systematic notes on Plecoptera: Anacroneuria proxima Klapálek (Plecoptera: Perlidae) - Stark, Bill P. (Acta entomologica slovenica (Ljubljana), 2001)
A gemale lectotype is designated for Acroneuria proxima Klapálek, 1923 and thespecies is redescribed. Anacroneuria crenulata Jewett, 1958 is placed as a junior synonym
Keywords: Mehika; Mexico; Plecoptera; vrbnice